ASPEK HUKUM PERDATA DALAM PENGEMBANGAN PARIWISATA BERBASIS BUDAYA DI KABUPATEN KARO MENURUT UNDANG-UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN - Terbit Terbit; Muhammad Ansori Lubis; Syawal Amry Siregar (JURNAL PROINTEGRITA, 2021)
Legal protection for visitors, both domestic tourists and foreign tourists, in Karo Regency has not been realized. Likewise with the contents of the tourism agreement between the Tourism and Culture Office of Karo District, Hal is still not optimal in presenting this agreement, this is evidenced by the fact that in Karo Regency, visitors who experience accidents in tourist locations are only the Gundaling tourist area which provides in the form of insurance while for other tourist areas have not yet formed legal protection in terms of safety and security.